Antioxidant from maize and maize fermented by Marasmiellus sp as stabiliser of lipid-rich foods - Daker, M.; Abdullah, N.; Vikineswary, S.; Goh, P.C.; Kuppusamy, U.R. (2008)
Mycelia of Marasmiellus sp. (KUM 50061) were grown on maize for antioxidant production. This formed the mycelial biomass which was then extracted with methanol. Antioxidant activity of methanolic extract was analysed by the TBARS assay, using egg yolk or palm cooking oil as a source of lipid, rather than the conventional rat liver microsomes or linoleic acid. Results showed that at low concentrations of extracts, inhibition of lipid peroxidation in buffered egg yolk was marginal, but significant inhibitory response was evident as the concentrations was increased. The concentration of extract of fermented maize that caused 50 inhibition of lipid peroxidation of buffered egg yolk was 6 mg/ml. Results also indicated a decrease in peroxidation in heated cooking oil supplemented with dried extract compared to unsupplemented cooking oil. The concentration range of dried extract supplementation was 0.2-5 mg/ml. Increasing the extract concentration did not significantly alter the inhibition of peroxidation. The inhibition effect was still evident even at the lowest concentration tested, and was found to be better than catechin and BHA. This pattern of observation was consistent over the 12-day period of observation. Therefore, the possibility of substituting synthetic antioxidants such as BHA and BHT, which are known to be carcinogenic, with antioxidants of natural origin is suggested. (c) 2007 Elsevier Ltd. All rights reserved.